Approaches to specialized genres - Lin, Kathy Ling; Mwinlaaru, Isaac N.; Tay, Dennis (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Approaches to Specialized Genres provides a timely update of the field of genre studies, with 14 cutting-edge contributions split into five sections using and integrating an exceptionally wide variety of methods and perspectives (such as ESP genre research, corpus linguistics, systemic functional linguistics, ethnographic and multimodal research) to analyse genres in written, spoken, visual and auditory modes across a multiplicity of pedagogic, professional and digital settings. It highlights and illustrates the growing trend of a multiperspective and inter-theoretic approach to genre studies and demonstrates how such methodological rigour can extend our knowledge of language, in general, and genres, in particular. It also examines a rich variety of underexplored genres such as the digital genre of synchronous videoconferencing, instructional slides, video ads, engineers' training log book entries, the narrative story genres, fundraising letters and retraction notices. It demonstrates not only the prominent value of genre research, but wide applications of genre knowledge in various educational and professional domains. The book brings together experts spreading across the world, including countries in South-East Asia, Europe, America, West Africa and South America. Accordingly, it will appeal to readers of diversified socio-cultural backgrounds working in all the aforementioned inter-related fields of applied linguistics and communication studies"--
OCLC-licensed vendor bibliographic record.
Keywords: Mass media genres; LANGUAGE ARTS & DISCIPLINES / Communication; LANGUAGE ARTS & DISCIPLINES / Linguistics